Persuading Minds: Propaganda and Mobilisation in Transylvania during World War I - Sima, Ana Victoria; Mihalache, Teodora-Alexandra (Peter Lang, 2018)
"The volume explores the phenomenon of propaganda in Transylvania during World War I. Propaganda messages targeted the entire population, using the available channels and institutions (in particular, Church and School). The studies included in this collection also analyse the feedback recorded among the multi-ethnic communities and the combatants."--Provided by publisher